SYNTHESIS OF ACETYLENE ALCOHOLS BASED ON ENANTIOSELECTIVE ETHYNYLATION OF KETONES WHICH HAVE VARIOUS NATURE (Scientific journal of the Fergana State University, 2023)
For the first time, terminal acetylene alcohols were synthesized by the enantioselective ethynylation reaction of some ketones using calcium carbide in the TBAF·3H2O/DMSO/H2O catalytic system. The influence of the nature and amounts of solvents, catalysts, reagents and substrates on product yield was studied. The most alternative conditions of control and direction of reactions are determined. The series of product formation efficiency of selected ketones was developed. Synthesized terminal acetylene alcohols were identified, their composition, purity, structure and specific constants were proved by modern physico-chemical methods.